341 RISK FACTORS FOR TUBERCULOSIS MORTALITY AT A LARGE URBAN MEDICAL CENTER. Issue 1 (1st January 2007) - Patel, A.; Barragán, M.; Blumberg, H. M.; Leonard, M. K.
Abstract : Background: Tuberculosis (TB) is the second leading cause of death worldwide by an infectious disease. TB cases in the United States are concentrated among underserved populations in the inner city. Grady Memorial Hospital (GMH) cares for 80% of patients with TB in Atlanta and 20% of all TB cases in Georgia. This study looks at the Metro-Atlanta, GA, population that accesses the Grady Memorial Hospital for health care. The primary purpose of the following study is to identify risk factors resulting in a death outcome of within a year of TB diagnosis. Methods: A matched case-control study was carried out looking at cases that died within 1 year of TB diagnosis between the years 1995 and 2005. The study population included persons between the ages of 18 and 65. Cases were matched to controls by year of diagnosis and if they outlived the 1 year since diagnosis. Results: In preliminary analysis of 250 patients, 40 cases and 40 controls were identified. The mean age of the study population was 49 (median = 50; range = 30-62) years. There were 62 (77.5%) males and 18 (22.5) females. The odds ratio was significantly different among cases and controls with extrapulmonary TB, 3.143 (95% CI = 1.12, 8.8; p < .0262). Among the 40 cases, 18 (45%) were current alcohol users compared with 11 (28%) in controls. Additionally, 11 (28%) of cases were current cocaine users compared with 7 (17.5%) in controls. Six (15 %) of the cases were also current IV drug users compared with 7 (17.5%) in controls. Both cases and controls had equal amounts of cigarette users (22, 55%). Furthermore, both cases and controls had an equal distribution of HIV-positive patients (27, 67.5% and 26, 65%). Conclusions: There is a significant difference in the frequency of cases with extrapulmonary TB compared with the controls. Although the odds ratios are not significant between the death outcome and risk factors of alcohol, cocaine, IV drug use, and cigarette use, one possible reason is that these may be markers for other socioeconomic risk factors that contribute to TB mortality. Although the risk factors above do not correlate strongly with death, they do correlate strongly with getting the disease. TB mortality remains a serious public health concern in the inner city despite this being a treatable disease.